2011
DOI: 10.5551/jat.7666
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Enhanced Glycemic Control with Saxagliptin on Endothelial Nitric Oxide Release and CD40 Levels in Obese Rats

Abstract: Aim: Endothelial cell (EC) dysfunction contributes to insulin resistance in diabetes and is characterized by reduced nitric oxide (NO) release, increased nitroxidative stress and enhanced inflammation. The purpose of this study was to test the effect of improved postprandial glucose control on EC function in insulin-resistant rats as compared to fasting glucose (FG) changes. Methods: Obese Zucker rats were treated with 10 mg/kg/day saxagliptin, a dipeptidyl peptidase-4 (DPP4) inhibitor, for 4 or 8 weeks and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 32 publications
1
41
0
4
Order By: Relevance
“…However, it has been pointed out that the therapy can mainly control fasting glucose levels but cannot necessarily correct blood glucose fluctuation, especially when sulfo-months glycemic control by DPP-4 inhibition improved nitric oxide release and reduced inflammation in rats, accompanying corrected postprandial hyperglycemia [23]. Although endothelial function and atherosclerosis were not evaluated in the current study, it is possible that BOT with DPP-4 inhibitor provides some favorable effect on them in human patients.…”
Section: Discussionmentioning
confidence: 66%
“…However, it has been pointed out that the therapy can mainly control fasting glucose levels but cannot necessarily correct blood glucose fluctuation, especially when sulfo-months glycemic control by DPP-4 inhibition improved nitric oxide release and reduced inflammation in rats, accompanying corrected postprandial hyperglycemia [23]. Although endothelial function and atherosclerosis were not evaluated in the current study, it is possible that BOT with DPP-4 inhibitor provides some favorable effect on them in human patients.…”
Section: Discussionmentioning
confidence: 66%
“…6,7,28 Recurring themes reported in the effects of GLP1 and DPPIV inhibitors are changes in nuclear factor-B and nitric oxide production. 29 Regulation of K ATP channels and cAMP levels may also be involved. Manipulating the incretin axis may improve vasoreactivity in both rodents and humans.…”
Section: Article See P 2338mentioning
confidence: 99%
“…Ojima et al [97] showed that GLP-1 receptor agonist would inhibit ADMA development in the kidney of streptozotocin-induced DM rats. In addition, serum concentration of ADMA was sought with the DPP-4 inhibitor saxagliptin in an animal experiment [98] . The discoveries of that study indicate that the DPP-4 inhibitors could impact serum concentrations of ADMA.…”
Section: Adma and Incretin-based Drugsmentioning
confidence: 99%